Decision Support Information System For Provision of Assistance Street Vendors Using Business Facilities Simple Additive Weighting Method - Ari Waluyo (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
The purpose of this study was to design a decision support system for providing business facilities for street vendors using the web-based Simple Additive Weighting method. The research method used in this study is a qualitative method with a descriptive approach. Data collection techniques used are by observation, literature study and interviews that have a close relationship with the main problem and the system development method used is the waterfall system development method. From the results of the research conducted found that the subjectivity of decision-making assistance is only determined based on the evaluation of the data that is owned and does not have definite criteria so that decision-making assistance has not found maximum results. Decision support system for providing business facilities for street vendors using the Simple Additive Weighting method produces sub-criteria aspects and sub-criteria values, namely aspects of the residence, income aspects and aspects of dependents of school children, each criterion has an attribute to be used as a reference for granting assessment help.